2023
DOI: 10.1186/s12866-023-02773-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance profile of common uropathogens during COVID-19 pandemic: hospital based epidemiologic study

Abstract: Background Antimicrobial resistance has a direct impact on the ability to treat common infections, and this was worsened during the COVID-19 pandemic. Worldwide surveillance studies are lacking and resistance rates vary spatially, so frequent local surveillance reports are required to guide antimicrobial stewardship efforts. This study aims to report our common local uropathogens and their antibiogram profiles in our community during the COVID era. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Despite the fact that the COVID-19 pandemic was the primary cause of increased and inappropriate antimicrobial use [30], our study found no conclusive evidence of a rising trend of antimicrobial resistance as a result of the pandemic. Other studies have produced conflicting results, with some indicating that the pandemic was associated with an increase in VRE infection or colonization [31] while others discovered a decrease in VRE resistance during the COVID-19 pandemic [4,32].…”
Section: Discussioncontrasting
confidence: 94%
“…Despite the fact that the COVID-19 pandemic was the primary cause of increased and inappropriate antimicrobial use [30], our study found no conclusive evidence of a rising trend of antimicrobial resistance as a result of the pandemic. Other studies have produced conflicting results, with some indicating that the pandemic was associated with an increase in VRE infection or colonization [31] while others discovered a decrease in VRE resistance during the COVID-19 pandemic [4,32].…”
Section: Discussioncontrasting
confidence: 94%
“…Enterococcus spp . showed high resistance (100%) to clindamycin and teicoplanin, which is similar to the findings of Abdel Gawad et al [ 33 ]. Gram-positive bacteria showed considerably high resistance rates to Antibiotics in this study, which is incompatible with the investigation conducted by Ahmed et al [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar trends in antimicrobial resistance have been observed, such as substantial resistance rates to ciprofloxacin of 65% for Escherichia coli and 62% for Klebsiella pneumoniae and a 38% resistance rate to carbapenems for Klebsiella pneumoniae reported in Italy [ 34 ]. These figures underscore the heightened challenge of managing drug-resistant infections, intensified by the pandemic’s impact on antibiotic prescribing practices [ 35 ], and highlight the critical need for robust antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%